THE ANALYSIS OF FINANCIAL PERFORMANCE IN RISK SYSTEMATIC AND RETURN STOCK FOR MANUFACTURING COMPANIES LISTED IN INDONESIA STOCK SHARIAH INDEX (ISSI) - Mukhyi, Ramdani Abdullah; Hwihanus, Hwihanus; Ratnawati, Tri (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2021)
The purpose of this research is to examine and analyze the effect of financial performance (liquidity, activity, leverage, growth, and profitability) on the systematic risk and return of Islamic stocks in the Indonesian Islamic stock index. This research data is gathered from annual reports on manufacturing companies within the year 2017-2019. This research population is all manufacturing companies listed in the Indonesian Shariah Stock Index for the period 2017- 2019 by using the purposive sampling method. The research technique used is a regression with Structural Equal Model Partial Least Square (SEM-PLS) consists of Inner model, Outers model, and Weight relation. The test results showed that all tested variables were influenced by other variables and were significant except Liquidity against systematic risk. And Leverage against systematic risk showing that liquidity, Leverage, Profitability have a not significant effect on the systematic risk structure is rejected whereas hypotheses other research accepted